Multidimensional identification of tissue biomarkers of gastric cancer - Guo, Tiannan (2013)
Gastric cancer remains highly fatal due to a dearth of diagnostic biomarkers for early stage disease and molecular targets for therapy. Plasma membrane proteins, including cluster of differentiation (CD) proteins and receptor tyrosine kinases (RTKs), are a rich reservoir of biomarkers. Recognizing that interrogating plasma membrane proteins individually overlooks extensive interactions among them, we have systematically investigated the membrane proteomes and transcriptomes of six gastric cancer cell lines. Our data revealed aberrantly high expression of proteins whose functions accurately reflect the clinical phenotype of gastric cancer, and prioritized critical RTKs and CD proteins in gastric cancer. Expression of selected surface proteins was confirmed by flow cytometry and immunostaining of clinical gastric cancer tissues. Close to 90% of the gastric cancer tissues in a cohort showed up-regulation of at least one of four proteins, that is, MET, EPHA2, FGFR2, and CD104/ITGB4. All intestinal type gastric cancer tumors in this cohort overexpressed at least one of a panel of three proteins, MET, FGFR2, and EPHA2. This study reports the first quantitative global landscape of the surface proteome of gastric cancer cells and provides a shortlist of gastric cancer biomarkers.